2016
DOI: 10.1039/c6cy00572a
|View full text |Cite
|
Sign up to set email alerts
|

Copper nanoparticles supported on diamond nanoparticles as a cost-effective and efficient catalyst for natural sunlight assisted Fenton reaction

Abstract: A series of catalysts consisting in Cu nanoparticles (NPs) supported on diamond nanoparticles (D) was obtained by polyol reduction of Cu(NO3)2 in the presence of D. The best performing Cu/D catalyst was obtained using a D sample in which the commercial D was submitted to Fenton treatment to decompose amorphous soot matter impure fying commercial D and subsequent hydrogen treatment at 500 ºC to reduce oxygenated functional groups generated in the oxidative treatment at the D surface. Cu/D performs better than a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 43 publications
1
33
1
Order By: Relevance
“…Besides acids and bases, homogeneous and heterogeneous catalysis is currently dominated by the use of transition metals, either as free ions, coordination metal complexes, clusters or nanoparticles, acting as active sites. [1][2][3][4][5][6][7][8][9][10][11][12][13] Some of these transition metals are rare, there being issues of sustainability coming with such choices. There is a large incentive in finding alternative metalfree catalysts, based on abundant elements.…”
Section: Introduction and Scope Of The Reviewmentioning
confidence: 99%
“…Besides acids and bases, homogeneous and heterogeneous catalysis is currently dominated by the use of transition metals, either as free ions, coordination metal complexes, clusters or nanoparticles, acting as active sites. [1][2][3][4][5][6][7][8][9][10][11][12][13] Some of these transition metals are rare, there being issues of sustainability coming with such choices. There is a large incentive in finding alternative metalfree catalysts, based on abundant elements.…”
Section: Introduction and Scope Of The Reviewmentioning
confidence: 99%
“…In the field of metal NPs, Garcia and co-workers have reported that metal NPs exhibiting plasmonic absorption bands in the visible region such as Au [8], Ag [15] and Cu [16] supported on surface modified diamond (D) NPs are among the most effective -4 -catalysts to promote the heterogeneous (photo)Fenton reaction under visible and solar light irradiation even at quasi-neutral pH values. It is important to note that analogous (photo)catalysts using other carbonaceous supports such as graphite, activated carbon (AC) or multiwall-carbon nanotubes (MWCNTs) resulted in lower activity and/or efficiency for this process.…”
Section: Introductionmentioning
confidence: 99%
“…However, the narrow working pH range and low H 2 O 2 utilization rate remarkably limit the practical application of˙OH-based Fenton systems. [3][4][5][6][7] Compared to the˙OH-based Fenton system, the sulfate radical (SO 4˙− ) based Fenton-like system by activation of peroxymonosulfate (PMS) was reported as one of the promising alternatives due to its high efficiency at a wide pH range and low catalyst dosage. [8][9][10] Among various transition metal catalysts, Co was found to be very active for PMS activation to produce SO 4˙− .…”
Section: Introductionmentioning
confidence: 99%